New Paraquat Requirements - Frederick Fishel; Brett Bultemeier; Jay Ferrell (EDIS)
This revision addresses the mitigation measures being undertaken by the EPA which became new labeling requirements for all paraquat products November 14, 2019. https://edis.ifas.ufl.edu/pi279